Madly Marvelous : the Costumes of the Marvelous Mrs. Maisel. - Zakowska, Donna (Abrams, Inc., 2021)
From the award-winning costume designer of Amazon Prime Video's The Marvelous Mrs. Maisel, a collection of the show's costumes, with never-before-seen photography, sketches, production stills, and more Amazon Prime Video's Emmy- and Golden Globe-winning series The Marvelous Mrs. Maisel centers on Miriam'Midge'Maisel, a 1950s New York City woman whose seemingly perfect life suddenly takes an unexpected turn, taking her from a comfortable life on Riverside Drive through the basket houses and nightclubs of Greenwich Village as she embarks on a groundbreaking standup comedy career. Created by Amy Sherman-Palladino (creator and showrunner of Gilmore Girls), and starring Rachel Brosnahan, Alex Borstein, and Tony Shalhoub, The Marvelous Mrs. Maisel has garnered fan and critical praise alike, with much of the attention focused on the exquisitely designed period costumes.Madly Marvelous: The Costumes of The Marvelous Mrs. Maisel explores the inner workings of award-winning costume designer Donna Zakowska's process, as well as the many inspirations for the show's wardrobe, including period photography, American and European fashion trends, and the various cultures and countercultures of late-1950s New York. The clothes of Mrs. Maisel are gorgeous, authentically detailed, and carefully crafted. Illustrated with sketches, photographs from Zakowska's workspace, behind-the-scenes shots, and production stills, the book follows the series from season to season, showing how the vocabulary of fashion-context, style, color, cut, accessories, and more-is integral to defining and developing the characters in the show. Madly Marvelous is a must-have for fans of the show and fashionistas alike, providing readers with a curated and well-informed look at an integral period in fashion history.- Resumé vydavatel
Keywords: Marvelous Mrs. Maisel (televizní seriál); filmové kostýmy; kostýmní výtvarnictví; televizní seriály; dějiny módy -- 1951-1960; film costume; costume design; television serials; history of fashion; elektronické knihy; obrazové publikace; monografie; electronic books; pictorial works; monographs